Efficacy of Electroconvulsive Therapy for Comorbid Frontotemporal Dementia with Bipolar Disorder - Sean Paul; Jennifer Goetz; Jeffrey Bennett; Tessy Korah (Case Reports in Psychiatry)
Challenges encountered in the diagnosis and treatment of frontotemporal dementia (FTD) are further confounded when presented with comorbid psychiatric disorder. Here we report a case of progressive FTD in a patient with a long history of bipolar affective disorder (BAD) 1, depressed type. We also report beneficial effects of electroconvulsive therapy and its potential application in similar comorbid disorders.